Language Style of Delivering Da’wah Messages in the Youtube Channel ZAVILDA TV - Angriani, Rina; Faridah, Faridah (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
The evolution of advanced information technology is relatively fast. Because of this progress, people can now quickly gain knowledge through social media; many people use Youtube media to get information or entertainment. Zavilda TV's YouTube channel features various entertainment options, including experimental social entertainment. This study aims to find out the style of language for conveying da'wah messages in Zavilda TV's YouTube content entitled "DUA CEWE S3XY TATOAN INSYAF BECAUSE OF FEAR OF DEATH & CHOOSE HIJRAH!" In this study, the authors used a descriptive qualitative method and interpreted it using the theory of analysis of the Milles and Huberman model. The results of this research are that there is a way of delivering and style of da'wah language to research subjects, namely women who wear headscarves and veils, so that the subjects of this research have a sense of wanting to be aware and use them daily. This video has the most viewers compared to other videos, and there are also many negative comments from netizens (internet citizens) because it is considered that the social content of the experiment contains elements of intolerance